A case study of β- and δ-MnO2 with different crystallographic forms on ion-storage in rechargeable aqueous zinc ion battery. (20th November 2019) - Guo, Cong; Zhou, Qihao; Liu, Huimin; Tian, Shuo; Chen, Binglei; Zhao, Jian; Li, Jingfa
Abstract: β-MnO2 and δ-MnO2 submicrospheres with different crystallographic forms were parallelly synthesized via a facile way using MnCO3 submicrospheres as manganese source and template. Fine observation enclosed that the β-MnO2 and δ-MnO2 submicrospheres were composed of nanoparticles and nanosheets respectively. The performances of these samples as cathode for aqueous zinc ion batteries were investigated: the prepared β-MnO2 and δ-MnO2 submicrospheres exhibit an initial capacity of 100 and 126 mAh/g and preserve about 99% and 81% of their original capacity over 100 cycles at a current density of 100 mA/g, respectively. It is observed from the galvanostatic charge/discharge profiles that the majority of excess capacity for δ-MnO2 than β-MnO2 is contributed by the first discharge step referred to H + insertion process, as δ-MnO2 has lower charge transfer resistance and larger diffusion coefficient than β-MnO2 . We ascribe this to the larger layer space of δ-MnO2 which would benefit for the easily insertion/extraction of hydronium ions. For contrast, the β-MnO2 encounters a sluggish transportation of hydronium ion along with the breaking of H–H2 O bond during ion inserting. Graphical abstract: Image 1